Pengaruh Pembiayaan Bank Wakaf Mikro Terhadap Peningkatan Kesejahteraan Ekonomi Nasabah - Miftahur Rahman; Defi Widayanti (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
This research is intended to answer questions. As a result, micro finance must be maintained. The population in this study is 232 customers. Siharsimi Arikunto estimated sample size was 25, thus producing a sample of 58 respondents and sampling samples using the purposing sampling. His data collection methods with the spread of questionnaires interviews, and documentaries. And the data analysis uses simple regression. Research has shown that independent variables in the micro-wakaf bank are arbitrarily affected by people's increased economic well-being. It's based on the results of the calculations obtained value. T account > the table is ( 9.23 > 2.0025) with a value signifikansi 0'05. Thus the h1 hypothesis was accepted. According to data analysis, micro business flanking institution must be conducted as micro finance institution. The amount, the level of funds given. Has an influence on the business run by customers in their daily economic needs. So that in the increase in the business it self is still increasing, limites to additional capital. To add merchandise and try new businesses only used for consumptive purposes should be used as productive funds.